2010
DOI: 10.3402/fnr.v54i0.5141
|View full text |Cite
|
Sign up to set email alerts
|

Body fat and dairy product intake in lactase persistent and non-persistent children and adolescents

Abstract: BackgroundLactase non-persistent (LNP) individuals may be lactose intolerant and therefore on a more restricted diet concerning milk and milk products compared to lactase persistent (LP) individuals. This may have an impact on body fat mass.ObjectiveThis study examines if LP and LNP children and adolescents, defined by genotyping for the LCT-13910 C > T polymorphism, differ from each other with regard to milk and milk product intake, and measures of body fat mass.DesignChildren (n=298, mean age 9.6 years) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
2
14
1
1
Order By: Relevance
“…This aspect is of great importance and potentially provides a more direct link to understanding the role of the LCT gene and lactase production on BMI. While several other studies (Almon et al 2010;Corella et al 2011) have used dairy intake to elucidate the effects of the LCT gene on BMI, we consider counting servings of dairy to be potentially misrepresentative since dairy products can have a variety of calories, quantity, and lactose content, as previously mentioned. Other strengths of our study include an ethnically diverse sample, the inclusion of admixture estimates to control for population stratification, and very detailed body composition and anthropometric measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect is of great importance and potentially provides a more direct link to understanding the role of the LCT gene and lactase production on BMI. While several other studies (Almon et al 2010;Corella et al 2011) have used dairy intake to elucidate the effects of the LCT gene on BMI, we consider counting servings of dairy to be potentially misrepresentative since dairy products can have a variety of calories, quantity, and lactose content, as previously mentioned. Other strengths of our study include an ethnically diverse sample, the inclusion of admixture estimates to control for population stratification, and very detailed body composition and anthropometric measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed a positive association between the LP allele and BMI (Kettunen et al 2010;Corella et al 2011;Almon et al 2012); however, in children, association studies have shown increased dairy consumption in carriers of the LP allele but no marked association with BMI levels (Almon et al 2010). Additionally, others have described a negative association between dairy intake, regardless of fat content, and BMI (Slyper and Huang 2009), further implicating dairy products as both pro and anti-obesogenic (Remesar et al 1999;Berkey et al 2005;Skinner et al 2003;Lehtimäki et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…The discrepancy observed between genotype and phenotype may be attributed to the indirect methods used in the former study to determine hypolactasia (i.e., using clinical symptoms only). Moreover, some authors have demonstrated that some individuals with the C/C genotype are able to consume milk (especially during meals) without displaying symptoms of lactase nonpersistence [22]. Results obtained using genotyping are expected to be more precise, because the study subject is not exposed to environmental factors which may confound the results.…”
Section: Discussionmentioning
confidence: 99%
“…Daily milk intake is not strictly correlated with the LCT-13910C>T genotype, but some reports proved statistically significant relationships between these two factors [22]. For example, a study conducted by the Agricultural University of Poznań [24], based on a questionnaire about dairy product consumption, showed that almost half of Polish participants (47.6%) reported drinking milk at least 4 out of 7 days of the week.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping lactase deficiency was chosen as the most suitable method of selective screening for hypolactasia. [5,12,14] The high prevalence of a genotype of lactose intolerance among the Uzbek population belonging to the Turkish group of peoples living in Central Asia is probably linked to a weak penetration in this territory of the mutated alleles C/T and T/T of LCT gene. [15,16] As shown by previous studies, despite the high frequency of the genotype C/C-13910, 78% of the sample Uzbek population consumed fresh milk in their diet, mostly in small amounts.…”
Section: Resultsmentioning
confidence: 99%